Hibernate Search by Example. - Perkins, Steve (Packt Pub., 2013)
A step-by-step guide for getting started with Hibernate Search, employing a practical example application that will make readers quickly learn and use the excellent search capabilities that the Hibernate Search tool offers. This book is for any Java developer who wants to quickly and easily add feature-rich search capabilities to his/her custom applications. It is assumed that readers will have experience in Java development, and understand some basic relational database concepts. However, while core Hibernate experience is very helpful, it is not necessarily required.